An evaluation on farmland ecological service in Jianghan Plain, China –from farmers' heterogeneous preference perspective. (March 2022) - Yang, Xin; Zhou, Xiaohe; Shang, Guangyin; Zhang, Anlu
Highlights: A mixed logit model is employed to explore farmers' heterogeneous preference for the farmland ecological service. Farmers' WTP for farmland ecological value were influenced by their socio-demographical characteristics. The farmland ecological value in Jianghan Plain is obtained by combing choice modeling with benefit transfer model. Abstract: As one of the important ecosystems that guarantee human life, farmland ecological system contains huge ecological value, in addition to the economic value directly reflected by current market transactions. After selecting six attributes (farmland area, farmland fertility, irrigation water quality, air quality, biodiversity, and recreation value) representing farmland ecological service by using mixed logit model of choice modeling (CE). The study explored the farmland ecological service value and its spatial distribution in Jianghan Plain through the construction of a benefit transfer model. The results indicated that: (1) Farmers have shown obvious heterogeneous preference of the farmland ecological value. Among them, farmers show stronger preference for air quality and biodiversity of farmland than for fertility and air quality. (2) Based on the heterogeneity of farmers' willingness to pay (WTP), farmland ecological value per unit area in the surveyed area was estimated to 2076.59 yuan/hm 2 . The analysis of the influence mechanism showed that the years of farming and the awareness of tillage technology passed the significance test at the level of 1% and those had a negative effect on their WTP. (3) The farmland ecological service value per unit area fluctuates within the range of 720.95–3370.39 yuan/hm 2 among the 19 counties of Jianghan Plain, with a spatial increasing trend from west to east.